Observações sobre os correlatos acústicos do acento em Apurinã (Aruák): estudo de um caso - SANTOS, Benedito de Sales (Universidade Federal do Pará, 2017)
This article investigates the hypothesis of duration being an acoustic correlate of stress in Apurinã, taking into account the results given by other authors. Cross-linguistic studies have suggested such a correlation. In this study duration is investigated in unstressed syllables, and in ones bearing primary and secondary stress. The article reviews previous work on Apurinã stress and then presents and analyzes new data. These results suggest a correlation between duration and primary stress only, and raise questions about the phonetic nature of such a correlation. The results also raise a theoretical question in phonology, namely the status of syllables with nasal vowels, which seem to behave like heavy or bimoraic syllables.